236 E-Prescribing and Smart Antimicrobial Stewardship in Upper Limb Infections. (28th February 2022) - Rela, M.; Peberdy, D.; Heard, K.; Fok, R.
Abstract: Aim: Upper limb infections secondary to traumatic wounds, animal bites and other causes are a common reason for admission to the plastic surgery service for intravenous antibiotics. This audit investigated the compliance of treatment of upper limb infections with trust guidance. The guidance stipulated an antibiotic treatment duration of five to seven days total and microbiology advice suggested that in cases requiring multiple washouts, this should start from the date of the last surgical washout where pus was present. Method: There was retrospective sampling for four months using inpatient lists to include patients admitted for intravenous antibiotics for upper limb infections. Notes were requested by the secretaries and data was collected using patient notes, discharge summaries and electronic drug charts. Results: The analysis included twenty-seven suitable patients. All patients had the correct antibiotics prescribed according to guidance, however only 22% of patients had five to seven days total of antibiotics either from the start of therapy or from the date of last infected washout in those who underwent surgical treatment. 14/27 patients had more than seven days total antibiotics. 13/27 patients were discharged with an additional seven days of oral antibiotics regardless of the total duration. Conclusions: These infections are significantly over-treated with antibiotics, which has serious potential consequences for antimicrobial resistance. The findings of the audit prompted new trust guidelines to be produced and prescribing guidance was sent to the junior doctors to calculate the total antibiotic duration when preparing discharge summaries. There is a plan for re-audit in a few months' time.